Molluscum Contagiosum Virus Topoisomerase: Purification, Activities, and Response to Inhibitors - Hwang, Young (American Society for Microbiology, 1998)
Molluscum contagiosum virus (MCV), the only member of the Molluscipoxvirus genus, causes benign papules in healthy people but disfiguring lesions in immunocompromised patients. The sequence of MCV has been completed, revealing that MCV encodes a probable type I topoisomerase enzyme. All poxviruses sequenced to date also encode type I topoisomerases, and in the case of vaccinia virus the topoisomerase has been shown to be essential for replication. Thus, inhibitors of the MCV topoisomerase might be useful as antiviral agents. We have cloned the gene for MCV topoisomerase, overexpressed and purified the protein, and begun to characterize its activities in vitro. Like other eukaryotic type I topoisomerases, MCV topoisomerase can relax both positive and negative supercoils. An analysis of the cleavage of plasmid and oligonucleotide substrates indicates that cleavage by MCV topoisomerase is favored just 3′ of the sequence 5′ (T/C)CCTT 3′, resulting in formation of a covalent bond to the 3′ T residue, as with other poxvirus topoisomerases. We identified solution conditions favorable for activity and measured the rate of formation and decay of the covalent intermediate. MCV topoisomerase is sensitive to inhibition by coumermycin A1 (50% inhibitory concentration, 32 μM) but insensitive to five other previously reported topoisomerase inhibitors. This work provides the point of departure for studies of the mechanism of function of MCV topoisomerase and the development of medically useful inhibitors.